Rationalising Public Expenditure in the Slovak Republic - Gönenç, Rauf (OECD Economics Department Working Papers, 2004)
Over the past decade, public expenditure in Slovakia was characterised by substantial social transfers and high public sector wage expenses. This paper analyses the main features of Slovakia's public expenditure system, reviews expenditure trends, and discusses recent reform initiatives. The latter have concerned the introduction of medium-term budget projections, the switch towards performance-based budgeting, the limitation of extra-budgetary funds, the devolution of spending power to sub-central administrative units, changes to the public employment regime, and reforms of the social security system. These initiatives are critically assessed and a number of recommendations concerning implementation and further reform steps are developed ...